Association between state-level malpractice environment and clinician electronic health record (EHR) time. (10th March 2022) - Holmgren, A Jay; Rotenstein, Lisa; Downing, Norman Lance; Bates, David W; Schulman, Kevin
Abstract: Objective: Clinicians spend significant time working in the electronic health record (EHR). The US is an outlier in EHR time, suggesting that EHR-related work may be driven in part by the legal environment and threat of malpractice. To assess this, we evaluate the association between state-level malpractice climate and clinician time spent in the EHR. Materials and Methods: We use EHR metadata from 351 ambulatory care health systems in the United States using Epic from January–August 2019 combined with state-level data on malpractice incidence and payouts. We used descriptive statistics to measure variation in clinician EHR time, including total EHR time, documentation time per day, and after-hours EHR time per day. Multi-variable regression evaluated the association between clinicians in high malpractice states and EHR use. Results: We found no association between location in a state in the top-quartile of malpractice payouts and time spent in the EHR per day, time spent in the EHR outside of scheduled hours, or time spent documenting per day, except for a subgroup of the clinicians in the highest malpractice specialties, where there was a small increase in EHR time per day ( B = 6.08 min, P < 0.001) and time spent documenting notes ( B = 2.77 min, P < 0.001). Discussion: State-level differences in malpractice incidence are unlikely to be a significant driver of EHR work for most clinicians. Conclusion: Policymakers seeking to address EHR documentation burden should examine burden driven by other socio-technical demands on clinician time, such as billing or quality measurement.